Two‑way interaction effects of psychosocial factors during pregnancy on maternal quality of life in Ibadan, Nigeria: a cross-sectional study: 10.55131/jphd/2023/210220 - Wellington, Olubukola (Journal of Public Health and Development, 2023)
During pregnancy, women are exposed to various psychosocial stressors that affect their quality of life, but few studies have looked at them additively in non-western contexts. This study aimed to assess the shared and unique contributions of perceived stress, financial strain, intimate partner violence, food insecurity, and social support to maternal quality of life. Data were gathered from a cross-sectional sample of 519 pregnant women who received antenatal care at various primary health care centers in Ibadan, Nigeria. Independent effects of and two-way interactions between psychosocial stressors in predicting maternal quality of life were explored using hierarchical linear regression. Higher scores for the main effects of food insecurity (β = -0.52, p < 0.01) and social support (β = 0.11, p < 0.01) were most strongly linked to a lower and better quality of life, respectively. Further, the two-way interaction effects were significant for financial strain in combination with intimate partner violence (β = -0.18, p < 0.01) and food insecurity in combination with social support (β = 0.18, p < 0.01) contributing to lower quality of life. The findings of this study were supported by the social determinants of health model, which recognizes that a person’s socioeconomic environment and psychosocial state affect his or her health and life experiences. It is recommended that health care practitioners should incorporate assessments of clinical factors of gestation with those of psychosocial needs as part of routine antenatal care in order to develop appropriate women-centered interventions.